2016
DOI: 10.1155/2016/1034912
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and the Use of Disease-Modifying Therapies in Patients with Multiple Sclerosis: Benefits versus Risks

Abstract: The burden of multiple sclerosis (MS) in women of childbearing potential is increasing, with peak incidence around the age of 30 years, increasing incidence and prevalence, and growing female : male ratio. Guidelines recommend early use of disease-modifying therapies (DMTs), which are contraindicated or recommended with considerable caution, during pregnancy/breastfeeding. Many physicians are reluctant to prescribe them for a woman who is/is planning to be pregnant. Interferons are not absolutely contraindicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 54 publications
2
40
0
Order By: Relevance
“…As well, natalizumab was detected in all newborns' umbilical cord blood samples (n = 5) [26]. When natalizumab is taken at the time of pregnancy, it is mandatory to test fetuses for thrombocytopenia and anemia after the birth [27]. Natalizumab treatment could be maintained during pregnancy as it is a promising strategy.…”
Section: Natalizumabmentioning
confidence: 99%
“…As well, natalizumab was detected in all newborns' umbilical cord blood samples (n = 5) [26]. When natalizumab is taken at the time of pregnancy, it is mandatory to test fetuses for thrombocytopenia and anemia after the birth [27]. Natalizumab treatment could be maintained during pregnancy as it is a promising strategy.…”
Section: Natalizumabmentioning
confidence: 99%
“…Such management, based on previous open studies which postulated a reduction in the increased number of relapses in the postpartum period by intravenous administration of IgG [57,58], was not confirmed in randomised studies [59,60]. A prompt return to immunomodulatory treatment is recommended [61][62][63].…”
Section: Alemtuzumabmentioning
confidence: 99%
“…The rate of miscarriage, stillbirth and congenital abnormality are not increased in women with MS . Several studies have shown no increased risk of miscarriage in women with MS who are exposed to disease‐modifying therapies (DMTs) . The risk of congenital malformations of children born to women with MS is comparable to that in the general population .…”
Section: Effects Of Ms On Pregnancymentioning
confidence: 99%